Post-Planting Care Techniques for Mangrove Trees in the Kariangau Coastal Area of Balikpapan - Ain Sahara; Fitri Oktafiani; Iin Darmiyati (Poltanesa, 2026)
Mangrove ecosystems play a vital role in reducing coastal erosion, supporting marine biodiversity, and sustaining the livelihoods of coastal communities. However, many mangrove restoration programs, particularly maintenance activities, pay little attention to post-planting maintenance, which significantly impacts the long-term survival of seedlings and ecosystems. This study aims to describe and demonstrate post-planting mangrove tree care techniques implemented in the coastal area of ​​Kariangau, Balikpapan, through a community-based approach. These activities included environmental education, the planting of 100 mangrove seedlings, and systematic maintenance carried out over a three-month monitoring period. Post-planting care included the installation and placement of support poles, the removal of debris from tidal movements, and regular monitoring of the stability and growth of seedlings. The results of the study, which lasted approximately three months, showed good progress. The newly planted mangrove seedlings grew well due to the care provided. Each month showed new leaf growth, and the plants were strong against sea tides. Only 1-2 mangrove tree trunks were tilted/out of position, resulting in a 99% success rate for the care system. Therefore, additional support poles were added. In this regard, community participation in post-planting mangrove care is crucial. These findings highlight the importance of post-planting management as a crucial component of sustainable mangrove restoration programs in coastal areas.